2020
DOI: 10.3390/jrfm13030061
|View full text |Cite
|
Sign up to set email alerts
|

What Future for the Green Bond Market? How Can Policymakers, Companies, and Investors Unlock the Potential of the Green Bond Market?

Abstract: The green bond market is attracting new issuers and a more diversified base of investors. However, the size of the green bond market remains small compared to the challenges it is meant to address and to the overall traditional bond market. This paper is based on a unique methodology combining an extensive literature review, market data analysis, and interviews with a large spectrum of green bond market participants. We identify the current barriers explaining the lack of scalability of the green bond market: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 17 publications
2
95
0
4
Order By: Relevance
“…The urgent need to finance climate and environmental solutions makes green bonds attractive. In order to further develop the green bond market, Deschryver and Mariz (2020) proposed measures to unlock the potential of green bonds to finance the sustainability goals. Those measures include standardization of the green bond market, high standards of disclosure and reporting, development of synergies with other sectors and instruments, and facilitation of investment in emerging economies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urgent need to finance climate and environmental solutions makes green bonds attractive. In order to further develop the green bond market, Deschryver and Mariz (2020) proposed measures to unlock the potential of green bonds to finance the sustainability goals. Those measures include standardization of the green bond market, high standards of disclosure and reporting, development of synergies with other sectors and instruments, and facilitation of investment in emerging economies.…”
Section: Discussionmentioning
confidence: 99%
“…In the green bond area, Ehlers and Packer (2017) addressed issues related to green bond certification and the environmentally related financial risks of green bonds. Deschryver and Mariz (2020) proposed measures to overcome the challenges in the continued growth of the green bond market. Cochu et al (2016) also identified bottlenecks and proposed policy measures to facilitate green bond issuance.…”
Section: Select Literature On Green Bondsmentioning
confidence: 99%
“…In order to analyze the impact of green bonds on the profitability and financial structure of the project, we assume that, in the course of the investment, the sponsor redeems the old debt and issues green bonds by the same nominal amount. Although there are different categories of green bonds, most of them are non-recourse debt precisely because a SPV is formed to limit liability [12] (p. 269), [38,39]. Building on the fact that a non-recourse debt obligation restricts the lenders' ability to seek repayment if there is a default, [11] (p. 16) states that when the management's control benefits differ significantly between one project to another, but the relative capabilities to manage the projects are similar, limited resource financing will be optimal.…”
Section: Methodsmentioning
confidence: 99%
“…In practice, the European Investment Bank was the pioneer in issuing bonds with climate objectives, having issued in 2007 an amount of EUR 600 million, for the purpose of financing projects related to energy efficiency and the use of renewable energy. The following year, the World Bank, through the International Bank for Reconstruction and Development (IBRD), issued its first green bonds in the amount of approximately US$ 400 million (World Bank, 2015;Deschryver and Mariz, 2020;Flammer, 2020).…”
Section: Overview and Assignments Of The Green Bond Market In The Transition To A Low Carbon Economymentioning
confidence: 99%
“…Along with the GBP, another international standard for bond certification is the Climate Bond Standard (from the Climate Bonds Initiative). The certification is characterized as a process in which the bond receives the green label, which indicates that its revenues will be used to finance projects aligned with environmental or climate issues, which gives investors greater confidence, reducing the risk of greenwashing 6 (Deschryver and Mariz, 2020;Fender, et. al., 2019).…”
Section: Overview and Assignments Of The Green Bond Market In The Transition To A Low Carbon Economymentioning
confidence: 99%